Study of First Principles of Mg-Si Binary Systems as Precipitates from T6 Heat Treatment of AL-MG-SI ALLOYS - Deni Haryadi; Haris Rudianto (Department of Physics, Sebelas Maret University, 2020)
One of the purposes adding the two main alloying elements Si and Mg in small quantities (≈ 1%) on Aluminum is to form strengthening precipitates in aluminium alloy, which typically contribute with a fivefold strength increase from pure aluminum. In the last decades, the investigation has begun to understand the structure and formation of the different phases during heat treatment. An important precipitate in Al-Mg-Si Alloy is β